Champions or Helpers: Leadership in Curriculum Reform in Science - Johnson, Elizabeth; Bird, Fiona; Fyffe, Jeanette; Yench, Emma (Journal of University Teaching and Learning Practice, 2012)
This study describes the perceptions of embedded teaching and learning leadership teams working on curriculum reform in science teaching departments. The teams combined a formally recognised leader, School Director of Learning and Teaching, with a project-based, more junior academic, Curriculum Fellow, to better leverage support for curriculum reform. Teams were established on the principles of localizing support and maximising credibility with discipline staff. The core teams were supported by a larger Faculty team of Associate Dean Academic, academic developer, educational designer, first year coordinator and project manager. Key themes emerging from the collected data were the complementary roles of members of the team, different perceptions of leadership between the School Directors of Learning and Teaching and the Curriculum Fellows, the importance of acting locally within the disciplines and the synergistic value of working in a team. The combination of formal and informal leadership aggregated into the FSTE School teams offers a model to support sustainable improvement in science teaching and learning in higher education.